Pemberdayaan Remaja Melalui Usaha Cucian Sepeda Motor Salju di Sukodadi Kecamatan Sukarami Kota Palembang - Nopriansyah Nopriansyah (Social Science and Contemporary Issues Journal, 2023)
This research is entitled youth empowerment through a snow motorbike washing business in Sukodadi, Sukarami District, Palembang City. Against the background of the problem, there are still many teenagers who have not gotten a job, which in the current era is difficult to get the job they want, but their educational status is a problem in order to have a decent job in Sukodadi. The formulation of the problem in this study first is how to empower youth through a snow motorbike washing business in Sukodadi, Sukarami District, Palembang City. Inhibiting factors in empowering youth through the snow motorbike washing business in Sukodadi, Sukarami District, Palembang City. The study aimed to analyze youth empowerment through the snow motorbike washing business in Sukodadi, Sukarami District, Palembang City, and find out what factors are the obstacles in empowering youth through the snow motorbike washing business in Sukodadi, Sukarami District, Palembang City. The theory used in this research is the theory of community empowerment. The approach used in this research is qualitative. the type of research used is field research. The type of data used is qualitative data, thtoection technique in this study uses observation, interviews, and documentation and the data analysis technique used in this study is the Miles and Huberman model, namely data reduction, data presentation, and drawing conclusions or verification. The results obtained from this study were from empowering youth through a snow motorbike washing business in Sukodadi, Sukarami District, Palembang City, firstly teenagers must have graduated from school so they can focus on work. The two teenagers must also be over the age of 18 and have permission from their parents so that they can work without a burden. Third, there are inhibiting factors in empowering youth through the snow motorbike washing business in Sukodadi, Sukarami District, Palembang City.